Atomic‐Layer‐Deposited Amorphous MoS2 for Durable and Flexible Li–O2 Batteries. Issue 6 (29th May 2019) - Song, Ming; Tan, Hua; Li, Xianglin; Tok, Alfred Iing Yoong; Liang, Pei; Chao, Dongliang; Fan, Hong Jin
Abstract: Li–O2 batteries (LOB) potentially have the highest specific capacity among all types of metal‐ion batteries but suffer severely from cycle instability and low energy efficiency. In this work, an integrated cathode is fabricated that contains an amorphous MoS2 thin layer deposited on a 3D conductive carbon scaffold to improve the energy efficiency to ≈83% and cycle life up to 190 cycles. An advanced pressure‐tuned stop‐flow atomic layer deposition (ALD) method is employed to deposit a ≈5 nm thick amorphous MoS2 layer on carbon nanotube forest‐covered graphite foam. It is established that this integrated 3D cathode exhibits high catalytic activity for both oxygen reduction reaction and oxygen evolution reaction. The benefit of the ALD MoS2 in lowering the energy barrier is also supported by first‐principles calculations. Finally, quasi‐solid state flexible LOBs are also assembled that can be stably discharged up to 6 d. This new and rational design of cathode may provide a new direction for achieving high‐performance flexible Li–O2 batteries. Abstract : A durable and flexible Li–O2 battery is constructed based on atomic‐layer‐deposited amorphous MoS2 coated carbon nanotube forests on a 3D graphite foam basis. The composite cathode is relatively more stable upon long cycles and delivers high rate performance. Flexible Li–O2 batteries full cells are also demonstrated.